Maternal and Perinatal Outcome in Women having VBAC - Bushra Noor Khuhro; Shahina Zahoor; Rubina Hussain (ziauddin University, 2024)
Background: Caesarean section rate as a mode of delivery has been increasing in the recent years despite the three fold increased risk of mortality compared to vaginal deliveries. This study is conducted to determine the mode of deliveries and their maternal and fetal outcome. Objective: To determine the maternal and perinatal outcome in women having a VBAC (Vaginal Birth after Cesarean Section) and to assess the safety of VBAC. Methods: A total of 206 pregnant females fulfilling the inclusion criteria were selected via consecutive sampling. Patients with previous 1 LSCS were observed for outcome. This study was conducted at Department of Obstetrics and Gynecology, Ziauddin Hospital, Kemari Campus, Karachi employing case series over a period of one year. Results: Of the 206 patients 72.8% delivered vaginally. Of these 60% of the patients with VBAC had no maternal or perinatal complication while 27.8% has failed trial of labor and had emergency caesarean section due to different reasons .Approximately 13.6% of patients had impending uterine rupture while undergoing VBAC trial needing emergency LSCS with 1% complicated by scar rupture, 4% developed scar tenderness leading to emergency LSCS, 1% resulted in vaginal hematoma and 1% with cervical tear.The perinatal outcome in VBAC was a NICU admission of 6.9%; Meconium stain liquor: 6.8%; Fetal distress 1.9% and no perinatal death. Conclusion: is safe & good modality to reduce caesarean section rate and should be offered and conducted under close monitoring and is successful with few maternal and perinatal complications. Key Words: Caesarean Section, Fetal Outcome, VBAC.